Madrasah Terpadu Di Kabupaten Agam Dengan Pendekatan Arsitektur Rumah Gadang - Nina Elvina; Mira Dharma; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Agam Regency is one of the regencies at West Sumatra Province had a vision "Independently Agam and Civil Achievement" means the atmosphere of people’s lives that reflect Islamic personality have faith and devotion. As civil city, Agam Regency need a Islamic education fasility to create sustainable education from the level of Madrasah Ibtidaiyah (MI), Madrasah Tsanawiyah (MTs), to the level Madrasah Aliyah (MA) get excellent character and quality at Islamic sector. The design of this Integrated Madrasah applies the characteristics of Architecture.Rumah Gadang such as using stilts, bagonjong roof, round poles, material, colors, and ornaments as a reference in the design. Rumah Gadang such as using stilts, bagonjong roof, round poles, material, colors, and ornaments as a reference in the design. Research method used includes primary data in the form of observation and documentation as well as secondary data in the form of literature studies and comparative studies. The concept of Integrated Madrasah is "Lights" as a light and can be seen to provide comfort for its user. Rumah Gadang Architecture makes the appearance of Integrated Madrasah buildings more integrated with the surrounding environment. The application of gonjong on the roof, ornaments on the facade, and the impression of the stilts produces an Islamic education facility that presents the atmosphere of a traditional Minangkabau house.Keywords: Agam Regency, Intergrated Madrasah, Architecture of Rumah Gadang